THE ROLE OF BUREAUCRATIC LEADERSHIP IN IMPROVING EMPLOYEE WORK DISCIPLINE IN THE CIREBON CITY TRANSPORTATION DEPARTMENT - Maulina, Hana; Sutarjo, Moh; Nurfalah, Farida (Journal of Economic Development and Village Building, 2023)
This research aims to find out and examine the role of leadership in improving employee work discipline in the Cirebon City Transportation Service, whether it is going well or not. The research method used is a qualitative research method. Data collection techniques were carried out by means of observation, interviews and documentation. The location of this research is the Cirebon City Transportation Department. Researchers determined informants using purposive techniques. In this research, the informants were divided into two, namely key informants, Head of the Cirebon City Transportation Service and secondary informants, employees of the Cirebon City Transportation Service. Data analysis techniques, data collection, data reduction or simplification, data presentation, and drawing conclusions. Researchers obtained data and information obtained from various sources with in-depth knowledge, including the Head of Department and his employees. The results of research regarding the leadership role of service heads in improving employee work discipline in the Cirebon City Transportation Service must be able to improve work discipline so that employees work in accordance with the regulations in the Cirebon City Transportation Service.